Literature Review: Media Roda Suku Kata Untuk Meningkatkan Keterampilan Membaca Permulaan Tahun 2021–2026 - Dwinanto; Ngabiyanto; Decky Avrilianda; Nuni Widiarti (Universitas Muhammadiyah Magelang, 2026)
Proficiency in beginning reading serves as a cornerstone of elementary education, laying the groundwork for students’ academic development at subsequent stages. Among Grade I students across Indonesia, difficulties in early reading literacy remain a persistent challenge in many schools. This paper seeks to examine, through a systematic approach, how effective the Syllable Wheel media has been in supporting beginning reading acquisition among Grade I elementary students, drawing on studies published from 2021 to 2026. A Systematic Literature Review (SLR) guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework was employed as the research method, encompassing 25 national journal articles sourced from Google Scholar, SINTA, and the Publish or Perish application. Articles were carefully filtered through four PRISMA stages—identification, screening, eligibility, and inclusion—covering topical relevance, year of publication, and research quality. Bibliometric data obtained via Publish or Perish were also utilized to assess the scholarly impact and credibility of the reviewed studies. Findings indicate that wheel-based instructional media—whether referred to as the syllable wheel, reading wheel, or smart wheel—have consistently demonstrated positive outcomes, with average gains in learning mastery ranging from 20 to 55 percent compared to baseline performance. The effectiveness of these tools is largely attributed to their interactive, visual, and kinesthetic qualities, which tend to foster greater motivation, participation, and self-confidence among young learners. This review concludes that the Syllable Wheel constitutes a promising, child-friendly instructional tool for early reading in Grade I, provided that its use is thoughtfully tailored to meet the diverse learning profiles and needs of students.